Marta : A Novel - Orzeszkowa, Eliza, 1842-1910 (Book collections on Project MUSE., 2018)
Suddenly widowed, previously middle-class Marta Świcka--the heroine of this trailblazing Polish novel, available in English here for the first time--is left penniless and in a grim battle for her own survival and that of her small daughter. As she applied for job after job in Warsaw--portrayed here as an every-city, an unforgiving commercial landscape that could be any European metropolis of the time--she is told time after time that only men will be hired, that men need jobs because they are fathers and heads of families even as she struggles to feed her own. Marta burns with Eliza Orzeszkowa's feminist conviction that sexism was not just an annoyance but a threat to the survival of women and children. Originally published in 1873 and easily a peer of The Awakening and A Doll's House, Orzeszkowa's work anticipated the need for social safety nets and could be read as an indictment of current efforts to dismantle those very programs. Tightly plotted and exquisitely translated by Anna Gąsienica Byrcyn and Stephanie Kraft, Marta resonates beyond its Polish setting to find its place in women's studies and labor history, and among other works of nineteenth-century literature and literature of social change--back cover.